Prevalence and Associated Risk Factors of Vitamin D Deficiency Among Female Adolescents in Sulaimaniyah, Iraq: A Community-Based Cross-Sectional Study - Salih, Galawezh Jalal; Abdul Sahib, Sanaa (Journal of Contemporary Medical Sciences, 2024)
Objectives: This study aims to examine the prevalence and risk factors related to VD deficiency among female adolescents. Methods: This cross-sectional study was done in secondary and preparatory schools in Sulaimaniyah, Iraq, from May 2022 to July 2023. A total of 120 schools were included in the study, with a calculated sample size of 340 female adolescents using a probability multistage random sampling method. Data was collected through a validated questionnaire, and blood samples were analyzed for VD levels. Results: In a study of 340 female adolescents aged 14-18 years, the findings showed that 39.4% of participants had severe VD deficiency, 42.6% were deficient, and 17.9% had insufficiency. The mean VD level was 13.29±6.45 ng/mL. Seasonal variation significantly impacted VD level (p=0.001), with the highest levels seen in summer and the lowest in winter. Skin colour also significantly influenced VD level (p=0.020), as individuals with lighter skin have higher levels. There were positive correlations between VD levels, milk intake (r=0.138, p=0.011), and cheese consumption (r = 0.135, p=0.013). The use of sunscreen had mixed effects. Interestingly, there was a positive correlation between SPF 15 and VD level (r=0.132, p=0.015), while higher SPF values were associated with lower levels. Conclusion: The findings highlight the importance of seasonal adjustments, improved dietary habits, and lifestyle changes to address VD deficiency in the population effectively.